Chiral dynamics and Zitterbewegung of Weyl quasiparticles in a magnetic field - Xi-Dan Hu; Li-Yan Li; Zheng-Xin Guo; Zhi Li (New Journal of Physics, 2021)
The relativistic dynamical properties of chiral Weyl quasiparticles (WQPs) are investigated in a stationary magnetic field. The visualized evolution process of quasiparticles’ wavepackets has been calculated with different angles between the spinor and the magnetic field. The results reveal that the chiral WQPs feature anisotropic dynamics, which falls into two typical motion modes, i.e. directional drift (chiral magnetic effect) and periodic oscillation (chiral Zitterbewegung ). We theoretically find that the mechanism behind this interesting dynamical phenomenon is the special chiral relativistic Landau level. Since the frequency, amplitude and drift velocity of chiral WQPs can be controlled in a measurable range, one can expect the observation of the phenomenon in the cold atomic system.